If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x-1)2-2(x+2)2=-2x^2+4x+11
We move all terms to the left:
4(x-1)2-2(x+2)2-(-2x^2+4x+11)=0
We multiply parentheses
-(-2x^2+4x+11)+8x-4x-8-8=0
We get rid of parentheses
2x^2-4x+8x-4x-11-8-8=0
We add all the numbers together, and all the variables
2x^2-27=0
a = 2; b = 0; c = -27;
Δ = b2-4ac
Δ = 02-4·2·(-27)
Δ = 216
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{216}=\sqrt{36*6}=\sqrt{36}*\sqrt{6}=6\sqrt{6}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-6\sqrt{6}}{2*2}=\frac{0-6\sqrt{6}}{4} =-\frac{6\sqrt{6}}{4} =-\frac{3\sqrt{6}}{2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+6\sqrt{6}}{2*2}=\frac{0+6\sqrt{6}}{4} =\frac{6\sqrt{6}}{4} =\frac{3\sqrt{6}}{2} $
| -1=-3^2+n= | | 2x+2x=3x+4 | | 5+6(x-1)=36 | | 30x-(5×+4)=96 | | 2t+12=28 | | -7(-3+2x)=-6x-1 | | 1/3x²+3x+0=0 | | ....x(-8)=(-56) | | 1x-12=(12)-6 | | 36+-32=x0 | | 35-4x=4)-12 | | 3x2+5)-12=3x | | 8-3x=14-4x8−3x=14−4x | | 5y=+3(5)=25 | | x^2=1048 | | w2=9,w2+9=0 | | -14x-8=8+4x+4 | | 2(2+6x=12 | | -7(7-3v)=39-v | | 6+a=6(1+8a) | | 24+3x=30 | | 20+2v=-5(-6v-4) | | (v+1)²+(v-3)²=15 | | 5y+44=2y×8 | | 0.4(x−1)+1=0.5x | | 8(1+6r)=6r+8 | | Y(y-10)=-21 | | 39+3p=-7(8-3p)+p | | 5(x+1)¹/⁴=10 | | b²+6b-8=0 | | 7^1-2x=4 | | 3∙(2x-4)=24 |